Solve 3(2y -2 )+3=5yDownsm14 - 10 Answers
The only way to answer this question is to simplify: General question about this is what is Y?
I will teach on how to solve it step by step:
3(2y -2 )+3=5y ---->problem
First lets simplify it in its simplest form.how? you just multiply 3 to (2y-2)
and the answer would be:
6y-6+3=5y ---> since its already in its simplest form we can simplify all the numbers with the same varialble. How? since -6 and +3 is a whole number we just add them up. -6+3=-3
So our new equation is 6y-3=5y.
we need to transpose 5y and -3 in order to add them with a equal variable.(remember when your transposing their sign will be the opposite of the original).
our new equation is 6y-5y=3 --->add the numbers with same varialbe and we will arrive:
y=3 ---->this will be our final answer:
Now, if you want to check if your answer is wrong: you just have to substitute y=3 in our original equation:
3(2y -2 )+3=5y
15=15 since they are both 15 we can conclude that our y is equal to 3.
This have an easy solution.
first we will multiply 3 with the elements present in the bracket, which will make the answer look like this:
6y -6 + 3 = 5y
Now write in the simplifying form:
6y-3 = 5y
We will bring 5y to the left hand side and 3 to the right hand side which will interchange their signs.
now as 6y-5y = y
so y = 3.
This is your solution
This is an easy equation to solve.
Solve 3(2y -2 )+3=5y
multiply first to get (6y - 6) + 3 =5y
You can now remove the parentheses and subtract 6 from 3 to get 6y - 3 = 5y
Subtract 5y from both sides of the equation to get 6y - 5y - 3 = 0
6y - 5y is just y, so y - 3 = 0
Add 3 to both sides of the equation to get the final result: y = 3
3(2y - 2)+3 =5y
6y - 6 + 3 =5y
3(2.3 - 2)+3=5.3
hope it helpful
This is simple equation you can get the value of ' y ' by seeing only the equation no need to solve it.
the answer is y=3.
3 (2y - 2) + 3 = 5y
6y - 6 + 3 = 5y
-6 + 3 = -3
6y - 3 = 5y
6y - 5y = 3
y = 3
This is very simple question. Do not need to solve just look and you will get the answer as y =3...
3(2y-2) +3 = 5y
1. 6y-6+3 = 5y
2. 6y-5y = 6-3
3. y = 3
3 ( 2y - 2 ) + 3 = 5y
6y - 6 + 3 = 5y
6y - 5y = 6 - 3
y = 3
The answer is pretty simple its 3...